Analyzing and evaluation of effective parameters on sound transmission loss of the triple-layered acoustic panels with sound-absorbing middle layer - Mohammadi, Nader (International Journal of Engineering and Technology, 2015)
In this research, a triple-layered acoustic panel with sound-absorbing intermediate layer materials is modeled analytically in order to calculate the sound transmission loss in the normal incidence field. This information provides an appropriate platform for optimum noise control. In this paper, porous material is used as an absorbent layer between two elastic panels. In modeling these triple-layered panels, theory of wave propagation in porous materials is used and bounded boundary condition of the first elastic layer and unbounded boundary condition of the second elastic layer is applied. To validate the model, the results of this model are compared with the results of the Bolton. Comparison of results revealed very good compatibility. Here, the effect of the length of the air gap between the elastic layers, density and the material of the elastic plate, the thickness and vibro-acoustic properties of the intermediate porous material on the values of transmission loss is investigated.In a wide range of frequencies, increasing air gap, density of elastic panels and porous layer thickness, increase the transmission loss up to 10 dB. At frequencies above 10 kHz, a reduction in porosity, static Young's modulus, the loss coefficient, increasing bulk density of the solid phase, the factor of geometrical structure and viscosity of porous material, increase the sound transmission loss up to 15 dB.